The influence of formative assessment on academic performance: exploring the role of teachers’ emotional support - Junsheng Wu; Xin Yu (Frontiers in Psychology)
Formative assessment is widely recognised as a vital tool for improving student performance. However, how formative assessment effectively influences academic performance remains unclear. This study explores the mediating role of emotional support of teachers in this association. By reviewing the recent literature, we explore how formative assessment can indirectly influence student performance through the emotional climate created by teachers. The study was analyzed using a structural equation model to explore the impact of formative assessment on the academic performance of 280 middle-school students in the South Chinese region. The results showed a significant positive relationship between formative assessment and teachers’ emotional support, as well as a significant positive relationship between teachers’ emotional support and academic performance. Furthermore, we also confirmed that teachers’ emotional support plays a mediating role in the relationship between formative assessment and students’ academic performance. These implications illuminate the importance of integrating emotional support strategies into formative assessment to improve educational outcomes. Several limitations of this study are discussed (e.g., cross-sectional design, cultural constraints, and reliance on self-reported data).